UV-Induced Fluorescence Imaging Combined with YOLO26-Based Classification for the Potato Surface Condition Assessment - Riza, Dimas Firmanda Al; Hendrawan, Yusuf; Suzuki, Tetsuhito; Ogawa, Yuichi; Kondo, Naoshi (Department of Agro-industrial Technology, University of Brawijaya, 2026)
AbstractPotato surface feature identification accuracy is a crucial parameter in determining the effectiveness of post-harvest classification systems and product quality assurance. Conventional color imaging systems often face limitations in distinguishing surface defects due to overlapping reflectance characteristics in the visible spectrum. This study proposes a quantitative classification framework that combines ultraviolet (UV)-induced fluorescence imaging with a YOLO26s-based deep learning classification model to identify three potato tuber surface conditions: normal, greening, and skinning injury. The YOLO26s classification model was trained using fluorescence images to learn distinguishing surface features. The proposed model achieved a training accuracy of 0.871, a validation accuracy of 0.871, and a testing accuracy of 0.875, demonstrating consistent generalization performance across the dataset. These results show that combining fluorescence images with deep learning classification provides a reliable and scalable approach for automatic potato surface quality assessment. This framework demonstrates strong potential for practical implementation in industrial grading systems.Keywords: deep learning, fluorescence imaging, postharvest quality, potato defects, YOLO model AbstrakAkurasi identifikasi fitur permukaan kentang merupakan parameter penting dalam menentukan efektivitas sistem klasifikasi pascapanen dan penjaminan mutu umbi kentang. Sistem pencitraan warna konvensional sering menghadapi keterbatasan dalam membedakan cacat permukaan akibat tumpang tindih karakteristik reflektansi pada spektrum cahaya tampak. Penelitian ini mengusulkan kerangka klasifikasi kuantitatif yang menggabungkan pencitraan fluoresensi yang diinduksi ultraviolet (UV) dengan model klasifikasi deep learning berbasis YOLO26s untuk mengidentifikasi tiga kondisi permukaan umbi kentang, yaitu normal, kehijauan (greening), dan luka kulit (skinning injury). Model klasifikasi YOLO26s dilatih menggunakan citra fluoresensi untuk mempelajari fitur permukaan yang membedakan masing-masing kondisi. Model yang diusulkan mencapai akurasi pelatihan sebesar 0,871, akurasi validasi sebesar 0,871, dan akurasi pengujian sebesar 0,875, yang menunjukkan kinerja generalisasi yang konsisten pada dataset. Hasil ini menunjukkan bahwa kombinasi citra fluoresensi dengan klasifikasi deep learning memberikan pendekatan yang andal dan skalabel untuk penilaian kualitas permukaan kentang secara otomatis. Kerangka ini memiliki potensi yang kuat untuk diimplementasikan dalam sistem grading industri.Kata kunci: cacat kentang, deep learning, kualitas pascapanen, model YOLO, pencitraan fluoresensi